Analisis Pola Pembelian Konsumen Menggunakan Algoritma Apriori Pada Toko Cha Cha Mart - Herlly Oktariani; Intan Utnasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Cha Cha Mart store is a company engaged in the sale of basic commodities, which is in the city of Batam. The Cha Cha Mart store sells various types of products so that every day the Cha Cha Mart store conducts many transactions, the transaction data that occurs is not managed properly so that the accumulation of data in the database. One way that is used to utilize data that is piled up is to process the data using a priori algorithm calculation techniques which are part of data mining techniques. A priori algorithm is expected to help the Cha Cha Mart Store to determine the products that are often sold simultaneously and determine the placement of goods in accordance with consumer habits. The a priori algorithm calculation results are supported by the use of tanagra application. One of the algorithm techniques used is the analysis of high frequency patterns in which in this study all the rules have a lift value of more than 1 (one) support of 10% and 55% confidence so that it can be used as a reference to increase sales